SISTEM INFORMASI PERANCANGAN APLIKASI DATA RECORD TRAINING KARYAWAN - Roida Pakpahan; Yuni Fitriani; Asriani Asriani (JURNAL TEKNIK KOMPUTER AMIK BSI, 2018)
Abstract-Computerized system when ino has become a major requirement in order to improve company performance. PT.Bumitangerang Mesindotama is one of the cocoa providers. And currently PT. Bumitangerang Mesindotama has obstacles in processing employee data, including in the case of making reports, this is because the process of making a report must kroscek reset all documents, employee data still use the conventional system based on the file (paper base) so relatively difficult to obtain employee training history information so that the resulting report data is less accurate. Therefore PT.Bumitangerang Mesindotama requires an application program that can present information on employee data quickly and accurately that can improve the quality of employee work. Training data management is one of the important components in realizing an information system that starts from the process of: employee registration data entry, training type, training provider, user data, training history, training certificate, employee training data, and reports of employee training report , registration reports, and user data reports. Therefore, the author designed this program using Microsoft Visual Basic 6.0 and database using MySQL.Keywords: employees, database, training